Determinants of ten-year overall survival of acute myeloid leukemia: a large national cancer database analysis. Issue 4 (21st March 2022) - Khanal, Nabin; Shostrom, Valerie; Dhakal, Prajwal; Upadhyay Banskota, Shristi; Chaulagain, Chakra; He, Fiona; Mosalpuria, Kailash; Gundabolu, Krishna; Bhatt, Vijaya Raj
Abstract: Clinical trials do not routinely capture long-term overall survival (OS) in acute myeloid leukemia (AML). We utilized a large National Cancer Database (NCDB) to determine different factors affecting 10-year OS in AML. For patients, 18–59 years who were treated with chemotherapy only without upfront hematopoietic cell transplant (HCT), younger age, female, CBF AML, higher income, and private insurance conferred higher 10-year OS. Among patients, 18–59 years treated with chemotherapy and upfront HCT, younger age and private insurance conferred higher 10-year OS. In a Cox proportional hazard model, the likelihood of death decreased with younger age, fewer comorbidities, treatment at an academic center, private insurance, and use of multiagent chemotherapy. Our results demonstrate poor long-term OS even among younger patients and highlights disparities in leukemia care based on insurance type.